KOMUNITAS PLANKTON SEBAGAI BIOINDIKATOR PENCEMARAN PERAIRAN SUNGAI MUSI DI KECAMATAN GANDUS DAN KERTAPATI BERDASARKAN PASANG SURUT - Eka Rizki Meiwinda; marsi .; arinafril . (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT Industrial processing in Musi River can be impact to plankton community based on phytoplankton and zooplankton. This study was conducted during March until May 2015 to analyze of plankton community under different industrial wastewater pollution in Musi River. These experiment has been taken places in 5 station determined by purposive random sampling methods based under different industrial water pollution and tidal. The station were selected to collect plankton and water samples. The study revealed occurance of total 30 species among these, the highest overflowing found in station 4 for amount 22249,20 ind/L. The highest grade of diversity, and dominancy indices were found in station 3 for 2,14 and 0,77 and the higest grade of evenness indices were found in station 1 for 0,61. It was concluded from this study that the plankton population of Musi River is highly influenced by the discharge from different industrial effluents.Classify of water in station 1,3,and 5 was indicated C class in moderate pollutedÂ  and classify of water in station 2 and 4 was indicated in D class in high polluted. Â  Keyworsd : Plankton, Musi River, Pollution